Cases on emerging markets responses to the COVID-19 pandemic - Kovid, Raj K., 1972-; Kumar, Vikas, 1979- (Advances in business strategy and competitive advantage., 2022)
"The present book highlights the organizational response to COVID- 19 pandemic with the case studies in different functional and integrated level of business management, presenting systematic case studies developed on the work done by the organizations with a strategic focus on unique initiatives taken for balancing the interest of different stakeholders, for example, taking care of employee with nil operations and business development and adopting technologies to minimize the decline in sales"--